Peningkatan Kemampuan Motorik Kasar Anak Usia 4-5 Tahun Melalui Fun Games di KB Permata Sunnah Sidoarjo - Masruroh, Siti; Aulina, Choirun Nisak (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
Gross motor development is important in early childhood as it is the foundation for children's physical growth and skills in carrying out daily activities. At KB Permata Sunnah Sidoarjo, some children experience difficulties in gross motor skills, such as balance and coordination, which indicates a gap between actual conditions and expected development. This research aims to improve the gross motor skills of children aged 4-5 years through implementing fun games designed to stimulate physical activity in a fun way. Using the Classroom Action Research (PTK) method with the Kemmis and McTaggart model, this research involved 10 children as subjects. Data was collected through observation with a gross motor skills assessment sheet, and analyzed using percentages to assess the level of achievement. The results showed a significant increase from 40% in pre-cycle to 80% in cycle II, confirming that fun games effectively improve children's gross motor skills. The implication is that this method can be adopted in early childhood education to optimize children's physical development.